Single Clinical Isolates from Acute Uncomplicated Urinary Tract Infections Are Representative of Dominant In Situ Populations - Dana Willner (American Society for Microbiology, 2014)
ABSTRACT Urinary tract infections (UTIs) are one of the most commonly acquired bacterial infections in humans, and uropathogenic Escherichia coli strains are responsible for over 80% of all cases. The standard method for identification of uropathogens in clinical laboratories is cultivation, primarily using solid growth media under aerobic conditions, coupled with morphological and biochemical tests of typically a single isolate colony. However, these methods detect only culturable microorganisms, and characterization is phenotypic in nature. Here, we explored the genotypic identity of communities in acute uncomplicated UTIs from 50 individuals by using culture-independent amplicon pyrosequencing and whole-genome and metagenomic shotgun sequencing. Genus-level characterization of the UTI communities was achieved using the 16S rRNA gene (V8 region). Overall UTI community richness was very low in comparison to other human microbiomes. We strain-typed Escherichia-dominated UTIs using amplicon pyrosequencing of the fimbrial adhesin gene, fimH. There were nine highly abundant fimH types, and each UTI sample was dominated by a single type. Molecular analysis of the corresponding clinical isolates revealed that in the majority of cases the isolate was representative of the dominant taxon in the community at both the genus and the strain level. Shotgun sequencing was performed on a subset of eight E. coli urine UTI and isolate pairs. The majority of UTI microbial metagenomic sequences mapped to isolate genomes, confirming the results obtained using phylogenetic markers. We conclude that for the majority of acute uncomplicated E. coli-mediated UTIs, single cultured isolates are diagnostic of the infection. IMPORTANCE In clinical practice, the diagnosis and treatment of acute uncomplicated urinary tract infection (UTI) are based on analysis of a single bacterial isolate cultured from urine, and it is assumed that this isolate represents the dominant UTI pathogen. However, these methods detect only culturable bacteria, and the existence of multiple pathogens as well as strain diversity within a single infection is not examined. Here, we explored bacteria present in acute uncomplicated UTIs using culture-independent sequence-based methods. Escherichia coli was the most common organism identified, and analysis of E. coli dominant UTI samples and their paired clinical isolates revealed that in the majority of infections the cultured isolate was representative of the dominant taxon at both the genus and the strain level. Our data demonstrate that in most cases single cultured isolates are diagnostic of UTI and are consistent with the notion of bottlenecks that limit strain diversity during UTI pathogenesis.